Digital Forensic and Firewall Nexus: Exploring a Decade of Scholarly Output - Wati, Anindya Pramitaqwati; Purwaningsih, Sri Budi; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This article presents a meticulously curated dataset comprising 54 journal articles extracted from a pool of 579 documents on digital forensics and firewall technologies. Spanning 2002-2012, the dataset explores the intersection of these fields, emphasizing Computer Science, institutional contributions (notably from the University of East London), and global diversity in authorship. Peak periods in 2006 and 2008 underscore evolving scholarly output. Inderscience Publisher, notably through the "International Journal of Electronic Security and Digital Forensics," stands out as a significant platform. The absence of prolific authors hints at a diversified authorship landscape. This dataset offers a foundational resource for detailed analyses of the dynamic relationship between digital forensics and firewall technologies. Highlights : Scholarly Focus: Emphasizes Computer Science and the technological aspects of digital forensics and firewalls. Institutional Contributions: Highlights the University of East London as a prominent contributor. Global Perspective: Reflects diverse global authorship and identifies the United Kingdom as a hub for related research. Keywords: Digital Forensic, Cybersecurity, Academic Research, Firewall Technologies, Global Authorship